1985
DOI: 10.1002/j.1460-2075.1985.tb03736.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of E. coli K-12 to transport PhoE-LacZ hybrid proteins out of the cytoplasm.

Abstract: A phoE‐lacZ hybrid gene encoding the N‐terminal 300 amino acid residues of pre‐PhoE protein, fused to an almost complete beta‐galactosidase molecule was constructed in vitro. Cell fractionation experiments suggested that the hybrid gene product is transported to the outer membrane. However, by using immuno‐cytochemical labelling on ultra‐thin cryosections it was shown that the hybrid protein accumulated in the cytoplasm. Thus, it appears that: (i) data on the localization of hybrid proteins merely based on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 32 publications
7
44
1
Order By: Relevance
“…agreement with results from immunocytochemical labelling techniques but in contrast to cell fractionation data [4]. Apparently, standard cell fractionation techniques are not reliable when used to localize this kind of hybrid protein and aggregate formation (see section 3.1) may be responsible for the fractionation artifacts.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…agreement with results from immunocytochemical labelling techniques but in contrast to cell fractionation data [4]. Apparently, standard cell fractionation techniques are not reliable when used to localize this kind of hybrid protein and aggregate formation (see section 3.1) may be responsible for the fractionation artifacts.…”
Section: Discussionsupporting
confidence: 75%
“…Cell fractionation experiments suggested that the hybrid protein is efficiently translocated to the outer membrane. On the other hand, the protein was shown by immunocytochemical labelling techniques to accumulate in the cytoplasm [4]. Here, we confirm the cytoplasmic accumulation of this hybrid protein by using protease accessibility experiments.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Samples for ultrastructural studies were kept in a freeze-substitution unit (Balzers FSU 010, Bal-Tec) in 2% osmium tetroxide in anhydrous acetone at Ϫ90°C for 32 h, warmed up to Ϫ60°C within 3 h, kept at Ϫ60°C for 4 h, warmed up to Ϫ40°C within 2 h, and kept there for 4 h. After washing with acetone, the samples were transferred into an acetone-Epon mixture at Ϫ40°C, infiltrated at room temperature (RT) in Epon and polymerized at 60°C for 48 h. Samples for immuno/affinity labeling were processed in 0.5% acrolein (WT Vtc4 and ⌬vtc4) or uranyl acetate (WT Vtc3 and ⌬vtc3) in anhydrous ethanol using the same temperature/time schedule for freeze-substitution. After washing with ethanol, the samples were transferred into an ethanol-Lowicryl K11M mixture, infiltrated with the polar methacrylate resin Lowicryl K11M (Polysciences, Eppelheim, Germany), and polymerized by UV irradition at Ϫ40°C for 48 h. Immunolabeling was done as described previously (Tommassen et al, 1985;van Bergen en Henegouwen and Leunissen, 1986) using affinity-purified antibodies to Vtc3p (N-terminal SPX domain) or to Vtc4p. Anti-Vtc3p (rabbit, 0.5 g/ml in 0.1% acetylated BSA) and anti-Vtc4p (goat, 3.2 g/ml in 0.2% gelatin and 0.5% BSA in PBS) were detected via protein A labeled with 15-nm gold particles (the signal for anti-Vtc4p was enhanced with an anti-goat antibody in between).…”
mentioning
confidence: 99%